PERAN SERTA SISWA DALAM PENGEMBANGAN USAHA KESEHATAN SEKOLAH (UKS) DI SDN NGRINGIN DEPOK SLEMAN YOGYAKARTA - Asda, Patria (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT Every school has an important role to create and improve the health of students through Student Health Units can make an effort to create an environment